Opportunities for centralized regional mode of manure and sewage management in pig farming: The evidence from environmental and economic performance - Shi, Boyang; Yin, Changbin; Léonard, Angélique; Jiao, Jian; Di Maria, Andrea; Bindelle, Jerome; Yao, Zhizhen (Waste management (Elmsford), 2023)
[Display omitted] •Comprehensive evaluations of centralized bio-energy mode are quantified.•Up-scaling and transport optimization are adapted to environment and economy targets.•Optimal collection radius for pig waste less than 31.45 km is determined.•Applicability and feasibility can be obtained regards to multi-subjects.•Experience for centralized mode promotion can be provided to other similar regions. Pig breeding is moving toward more intensive development and is accompanied by the integrated generation of pig waste. This has disrupted the synergy between the original manure and sewage management mode and corresponding farmland at the household level. Centralized bio-energy mode is proposed to relieve environmental pressure, increase the resource recovery efficiency and rebuild the breeding and cropping. However, there is a lack of comprehensive information on a regional scale, particularly regarding evaluation, applicability and feasibility. Therefore, compared to the individual and traditional mode at the household level, this study was conducted using life cycle assessment and life cycle cost analysis, systematically assessed the environmental performance and economic viability of the centralized bio-energy mode at the regional scale, and further explored the adaptability of multi-subjects (various pig farms and biogas enterprise) and regional feasibility. Results revealed that the centralized bio-energy mode appeared to be a better alternative in terms of global warming, terrestrial acidification and marine eutrophication, with the significant reductions of 49.49 %, 6.8 % and 4.67 % respectively. Moreover, the study demonstrated a substantial profit of 48.5 CNY11CNY, Chinese yuan, 1 CNY=0.145 USD (1 April 2023). per ton of managed pig waste. Furthermore, both environmental and economic performance could be improved through scale expansion and transport optimization, with an optimal collection radius of less than 31.45 km. Conclusions clarified the potential of centralized bio-energy mode and provided valuable references for its implementation in various regions. Ultimately, further contributing to a more efficient, cost-effective, and regulated manner for resource recovery, culminating in the sustainability of pig farming and achieving environmental-friendly agriculture practices in regional contexts.